In vitro RNA transcription by the New Jersey serotype of vesicular stomatitis virus. I. Characterization of the mRNA species. - Franze-Fernandez, M T (1978)
The in vitro RNA synthesis by the virion-associated RNA polymerase of vesicular stomatitis virus (VSV), New Jersey serotype, was compared with that of the serologically distinct Indiana serotype of VSV. The New Jersey serotype of VSV synthesized five distinct mRNA species in vitro, three of which were smaller than the corresponding species synthesized by the Indiana serotype of VSV. These included the mRNA's coding for the G, M, and NS proteins. By hybridization experiments, virtually no sequence homology was detected between the mRNA's of the two serotypes. Despite this lack of overall homology, the 12 to 18S mRNA species of both serotype contained a common 5'-terminal hexanucleotide sequence, G(5')ppp(5')A-A-C-A-G. The signicance of this finding in light of specific interactions between the two serotypes of VSV in vivo is discussed.